Effect of crevice corrosion inhibitors on the passivity of alloy 22 - Ortíz, Mauricio Rincón; Rodríguez, Martín Alejandro; Carranza, Ricardo Mario (Journal of The Electrochemical Society)
Electrochemical impedance spectroscopy (EIS) tests were performed on alloy 22 in chloride and chloride plus inhibitor naturally aerated solutions, at 90°C. A Rω-(RF//CPE) equivalent circuit model was used for fitting to the EIS data. Rω and RF were the ohmic and film resistances, respectively, and CPE accounted for the non-ideal capacitance. The fitting errors of the circuit parameters decreased as pH increased. The passive film properties improved as pH increased from pH 0 to pH 4. At higher pH values, the passive film properties depended mainly on the identity of the salt added. Oxalic, picric and citric acids additions were detrimental for the passive film developed on alloy 22. Carbonate and bicarbonate led to less protective passive films only when added to 1 M NaCl solutions. Fluoride was a detrimental addition at pH 6, but not at pH 9. Acetic acid, carbonic acid, silicate, tungstate, and molybdate additions did not modify significantly the protective properties of the alloy 22 passive film. Nitrate, sulfate and chromate additions led to thick and protective passive films. The efficiency of the tested species as crevice corrosion inhibitors was not related to their effects on alloy 22 passivity. Fil: Ortíz, Mauricio Rincón. The University Of Akron (uoa); Fil: Rodríguez, Martín Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina Fil: Carranza, Ricardo Mario. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina